Strategi Restrukturisasi Utang dalam Kasus Garuda Indonesia: Pendekatan PKPU - Utami, Nabila Ratu; Paranna, Tri Nadia Samuel; Suryani, Nyulistiowati; Yuanitasari, Deviana (DOKTRINA: JOURNAL OF LAW, 2024)
Debt restructuring through PKPU has a significant impact on creditors and debtors. Debt restructuring can provide benefits, such as better debt repayment than bankruptcy. However, debt restructuring also has disadvantages, including large time and costs. For the success of restructuring, the debtor's good faith is very necessary. The PT Garuda Indonesia case shows that debt restructuring was successful through a series of steps, including the issuance of debt securities and sukuk, and involving various parties such as the government and investors. The advice given is that the Early Warning System for PT's finances needs to be strengthened. Garuda Indonesia so that problems can be immediately identified and handled before they escalate. Apart from that, there is a need for effective legal regulations to avoid bankruptcy in resolving debt and receivable cases. To get around this, you can apply PKPU, which stands for postponing debt payment obligations, as a rule. After the debtor's assets are liquidated, the second option is to teach creditor-debtor reconciliation in court.